The RETURN OF THE MOTHER-FIGURE IN CARSON MCCULLERS’ "THE BALLAD OF THE SAD CAFÉ" - Mahdavi Nejhad, Mohammad Hossein; Alizadeh, Ghiasuddin; Amani, Omid (Armenian Folia Anglistika, 2024)
Carson McCullers’ The Ballad of the Sad Café is a mysterious novella depicting the clash between masculinity and femininity and their strife for dominance in a southern patriarchal society. In the midst of this quarrel, the arrival of the effeminate Cousin Lymon to the town marks the emergence of a new atmosphere. Since the Ballad is similar to many American literary works which delineate the father-figure as either absent or weak, and with reference to Gilles Deleuze’s vitalist-inspired philosophy, this article aims to argue that the arrival of Lymon to the town is reminiscent of the return of the mother-figure, which entails creativity and birth. With Lymon’s becoming-woman, an immense change pervades the town and Miss Amelia’s café; however, as the society of brothers is always under the threat of the return on the part of the father figure, with Marvin Macy’s return from the penitentiary, a block of becoming barricades any further flourish of brotherhood, and sanguinity gives its place to annihilation. Here, once the banner of becoming-woman, Lymon grabs this opportunity to conspire with the father-figure in order to break the fixity of the café and guarantee his nomadic flow.